ACSM's guidelines for exercise testing and prescription - Riebe, Deborah; Ehrman, Jonathan K. 1962-; Liguori, Gary 1965-; Magal, Meir (Wolters Kluwer, 2018)
This handbook delivers scientifically based standards on exercise testing and prescription to the certification candidate, the professional, and the student. This manual gives summaries of recommended procedures for exercise testing and exercise prescription in healthy and diseased patients The tenth edition reflects some crucial and exciting changes, making the content necessary for effective study and practice. New pre-exercise health screening recommendations are critical to helping more of the population begin a safe, healthy physical activity program without consulting a physician. New and expanded information on the risks of sedentary behavior, clinical exercise testing and interpretation, high intensity interval training, musculoskeletal injury risk, fitness testing protocols and norms, and an expansion of the principles of health behavior change are included. Additionally, significant reorganization of content will help you reach the information you need quickly.